Extraction of local coordination structure in a low‐concentration uranyl system by XANES. (1st April 2016) - Zhang, Linjuan; Zhou, Jing; Zhang, Jianyong; Su, Jing; Zhang, Shuo; Chen, Ning; Jia, Yunpeng; Li, Jiong; Wang, Yu; Wang, Jian-Qiang
Abstract : A simple and reliable method of obtaining local geometric structural information around a uranium absorber in uranyl species by quantitative XANES analysis was developed. Abstract : Obtaining structural information of uranyl species at an atomic/molecular scale is a critical step to control and predict their physical and chemical properties. To obtain such information, experimental and theoretical L 3 ‐edge X‐ray absorption near‐edge structure (XANES) spectra of uranium were studied systematically for uranyl complexes. It was demonstrated that the bond lengths ( R ) in the uranyl species and relative energy positions (Δ E ) of the XANES were determined as follows: Δ E 1 = 168.3/ R (U—Oax ) 2 − 38.5 (for the axial plane) and Δ E 2 = 428.4/ R (U—Oeq ) 2 − 37.1 (for the equatorial plane). These formulae could be used to directly extract the distances between the uranium absorber and oxygen ligand atoms in the axial and equatorial planes of uranyl ions based on the U L 3 ‐edge XANES experimental data. In addition, the relative weights were estimated for each configuration derived from the water molecule and nitrate ligand based on the obtained average equatorial coordination bond lengths in a series of uranyl nitrate complexes with progressively varied nitrate concentrations. Results obtained from XANES analysis were identical to that from extended X‐ray absorption fine‐structure (EXAFS) analysis. XANES analysis is applicable to ubiquitous uranyl–ligand complexes, such as the uranyl–carbonate complex. Most importantly, the XANES research method could be extended to low‐concentration uranyl systems, as indicated by the results of the uranyl–amidoximate complex (∼40 p.p.m. uranium). Quantitative XANES analysis, a reliable and straightforward method, provides a simplified approach applied to the structural chemistry of actinides.